Female identities in lesbian web series : transnational community building in Anglo-, Hispano-, and Francophone contexts - Obermayr, Julia, 1981- (Queer studies, 2020)
Lesbian web series narrate female-centered stories, strengthen identity construction, and generate transnational communities beyond cultural barriers. Julia Obermayr explores the first definition of a new format, the first representations of lesbian women in US-American, Canadian, and Spanish web series from 2007 and onward, as well as their reciprocal effects regarding identity construction and community building of their transnational, mainly female, audience.The analyzed corpus comprises scenes taken from Venice the Series (2009) and its backstory »Otalia« on the soap opera Guiding Light (1952-2009), Seeking Simone (2009), Out With Dad (2010), Féminin/ Féminin (2014), Chica Busca Chica (2007) and its cinematic sequel De Chica En Chica (2015), as well as Notas Aparte (2016).